High performance VLSI signal processing: Innovative architectures and algorithms Volume 2 - Systems design and applications - Villagarcía Wanza, Horacio Alfredo (2004)
One of the major breakthroughs in VLSI technology has been its ability to implement signal processing algorithms and architectures onto cost-effective ASIC and DSP chips.\nWorks in this area are highly interdisciplinary; they involve interaction among areas such as VLSI and circuit design, computer architecture, signal processing, communications and computer-aided design.\nThe editors collect in two volumes much of the research efforts and findings that have made the high performance implementation of signal processing possible in the '90s.